Targeting phosphoglycerate kinases by tatridin A, a natural sesquiterpenoid endowed with anti-cancer activity, using a proteomic platform - Ferraro, Giusy; Voli, Antonia; Mozzicafreddo, Matteo; Pollastro, Federica; Tosco, Alessandra; Monti, Maria Chiara (Frontiers in Molecular Biosciences, 2023)
Tatridin A (TatA) is a germacrane sesquiterpenoid containing one E-and one Z-double bond in its 10membered ring which is fused to a 3-methylene-di-hydrofuran-2-one moiety. TatA bioactivity has been poorly investigated despite its interesting chemical structure. Here, a functional proteomic platform has been adapted to disclose its most reliable targets in leukemia monocytic cells and Phosphoglycerate Kinases were recognized as the most affine enzymes. Thanks to a combination of limited proteolysis and molecular docking, it has been discovered that TatA interacts with the active domains of Phosphoglycerate Kinase 1 altering its hinge region and it can be accountable for TatA inhibition potency on the enzyme activity. A more detailed TatA biological profile showed that it is fully active also against gastric cancer cells, downregulating mRNA levels of the chemokine receptor 4 and βcatenin and inhibiting the invasiveness of living KATO III cells as a direct consequence of Phosphoglycerate Kinase 1 antagonism.